A Deadly Combination: Depression and Suicide in the Presence of Cancer - Perez Jalessa; Overholser James; Athey Alison; Ornan Gili; A. Stockmeier Craig; Lehmann Jennifer; Dieter Lesa (Journal of Psychological Disorders, 2018)
The present study was designed to examine differences among cancer patients who died by medical/natural causes or by suicide. This study aims to identify protective and risk factors for suicide in individuals who have been diagnosed with cancer. Unlike previous studies that examined suicidality in cancer patients, our study did not find significant differences between patients with a cancer diagnosis at TOD who died by suicide and those who died by natural or medical causes.
Keywords: Suicide